Psoriasis comorbidities: complications and benefits of immunobiological treatment - André Vicente Esteves de Carvalho; Ricardo Romiti; Cacilda da Silva Souza; Renato Soriani Paschoal; Laura de Mattos Milman; Luana Pizarro Meneghello (Sociedade Brasileira de Dermatologia, 2016)
Abstract During the last decade, different studies have converged to evidence the high prevalence of comorbidities in subjects with psoriasis. Although a causal relation has not been fully elucidated, genetic relation, inflammatory pathways and/or common environmental factors appear to be underlying the development of psoriasis and the metabolic comorbidities. The concept of psoriasis as a systemic disease directed the attention of the scientific community in order to investigate the extent to which therapeutic interventions influence the onset and evolution of the most prevalent comorbidities in patients with psoriasis. This study presents scientific evidence of the influence of immunobiological treatments for psoriasis available in Brazil (infliximab, adalimumab, etanercept and ustekinumab) on the main comorbidities related to psoriasis. It highlights the importance of the inflammatory burden on the clinical outcome of patients, not only on disease activity, but also on the comorbidities. In this sense, systemic treatments, whether immunobiologicals or classic, can play a critical role to effectively control the inflammatory burden in psoriatic patients.